Burden of hepatitis C virus infection in India: A systematic review and meta‐analysis. Issue 2 (26th September 2018) - Goel, Amit; Seguy, Nicole; Aggarwal, Rakesh
Abstract: Background and Aim: Burden of hepatitis C in India is not known. We therefore conducted a systematic review of the available data on anti‐hepatitis C virus (HCV) seroprevalence in the Indian population. Methods: We searched several publication databases for English language papers that reported data on anti‐HCV seroprevalence from India and also identified other unpublished sources of such data. Data on groups likely to represent seroprevalence in general population and in selected high‐risk groups were extracted and subjected to meta‐analysis. Results: Of the 3995 published papers and 94 additional data sources identified, 327 were selected; these provided 414 anti‐HCV seroprevalence data points. Pooled anti‐HCV seroprevalence rates in community‐based studies, blood donors, and pregnant women were 0.85% (95% confidence interval: 0.00–3.98%), 0.44% (0.40–0.49), and 0.88% (0.21–1.90), respectively. Among groups considered at high risk of HCV, pooled anti‐HCV seroprevalence rates were as follows: people living with HIV (40 studies from 17 states: 3.51% [2.43–4.76]), persons on maintenance hemodialysis (37, 13; 19.23% [13.52–25.65]), people who inject drugs (46, 14; 44.71% [37.50–52.03]), multi‐transfused persons (38, 12; 24.06% [20.00–28.36]), persons with sexually transmitted diseases (7, 5; 4.10% [0.98–9.04]), and those with high‐risk sex behavior (6, 5; 4.06% [1.79–7.10]). Conclusions: Community‐based data on HCV seroprevalence in India were limited. Large amount of data on blood donors and pregnant women were identified, with pooled anti‐HCV seroprevalence rates of 0.44% and 0.88%, respectively. Among high‐risk groups, anti‐HCV prevalence was higher among people living with HIV, those with sexually transmitted diseases, high‐risk sex behavior or injection drug use, and those receiving hemodialysis or frequent transfusions.